Distribution of Lithophyllum kuroshioense sp. nov., Lithophyllum subtile and L. kaiseri (Corallinales, Rhodophyta), but not L. kotschyanum, in the northwestern Pacific Ocean. Issue 6 (2nd November 2019) - Kato, Aki; Baba, Masasuke
ABSTRACT: Lithophyllum kotschyanum had been widely reported across the tropical Red Sea and the Indo-Pacific Ocean based on morpho-anatomical identification. We conducted a taxonomic study, based on morpho-anatomical and gene sequence data ( psb A, rbc L, COI and LSU), of branched Lithophyllum specimens ascribed to L. kotschyanum in Japan and the Philippines, and of the type specimen of L. kotschyanum f. subtilis described from the Caroline Islands, a taxon not yet revised in a modern context. Sequence comparisons could not confirm the presence of L. kotschyanum, and instead, recognised L. kuroshioense sp. nov . and L. subtile comb. & stat. nov . in addition to a widespread tropical taxon, L. kaiseri . The three species shared warty to fruticose thalli. Lithophyllum kuroshioense is morpho-anatomically distinguished from L. kaiseri by the trichocyte occurrence (rare vs abundant) and proportion of sunken tetra/bisporangial conceptacle roofs (22.8% vs 1.8%). Lithophyllum subtile is morpho-anatomically distinct from L. kaiseri and L. kuroshioense by its comparatively smaller tetra/bisporangial conceptacle chamber diameters (192–293 µm vs 268–390 µm and 263–400 µm, respectively) and by its shorter pore canal lengths (11–46 µm vs 40–86 µm and 40–71 µm, respectively). Trichocyte development is of the Jania rubens -type in L. kuroshioense, and of the Metagoniolithon -type in L. kaiseri and L. subtile . This study showed that at least three branched, trichocyte-bearing species of Lithophyllum occur in the northwestern Pacific Ocean, none of which is L. kotschyanum .